2004
DOI: 10.1111/j.1559-1816.2004.tb02541.x
|View full text |Cite
|
Sign up to set email alerts
|

Who's Watching the Race? Racial Salience in Recruitment Advertising1

Abstract: A recent finding (Thomas & Wise, 1999) suggested that the race of organizational representatives may be more important to minority applicants than to White applicants. Consequently, this study empirically examines the impact of race in recruitment advertising on applicant attraction. Participants (N= 194) were recruited in 3 field settings and were exposed to recruitment literature varying the race of a depicted organizational representative. Results indicate that Black and Hispanic participants were more attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
125
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(133 citation statements)
references
References 37 publications
8
125
0
Order By: Relevance
“…If the person is perceived as similar to them, favorable reactions toward the job and the advertising organization are enhanced: For example, Perkins et al (2000) found that African Americans felt more attracted by a racially diverse group of employees depicted in the advertisement than by homogeneous white employees. Also, Avery et al (2004) observed racial congruence effects for African Americans when viewing recruitment advertisements. Similarly, a gender congruent role model might foster such favorable reactions.…”
Section: Introductionmentioning
confidence: 99%
“…If the person is perceived as similar to them, favorable reactions toward the job and the advertising organization are enhanced: For example, Perkins et al (2000) found that African Americans felt more attracted by a racially diverse group of employees depicted in the advertisement than by homogeneous white employees. Also, Avery et al (2004) observed racial congruence effects for African Americans when viewing recruitment advertisements. Similarly, a gender congruent role model might foster such favorable reactions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, an organization may feature minority representatives in a job advertisement to signal its commitment towards diversity (Perkins et al 2000;Rynes 1991;Spence 1973). Past research has shown that minority (e.g., African American) applicants rated an organization featuring a group of African American representatives as more attractive than an organization featuring a group of Caucasian representatives (Avery 2003;Avery et al 2004;Perkins et al 2000;Wells 2008).…”
mentioning
confidence: 96%
“…To date, there are four studies that have examined the effect of race composition on attraction (Avery 2003;Avery et al 2004;Perkins et al 2000;Wells 2008). These studies consistently showed that minority applicants are more attracted to organizations featuring a group of minority representatives than organizations featuring a group of majority representatives.…”
mentioning
confidence: 99%
“…In this way, attention to diversity permeates every organizational action. As Avery, Hernandez, and Hebl (2004) such, deep differences in organizational culture may influence the expression of diversity in an organization. Examining diversity through Schein's lens of artifacts, values, and assumptions provides an interesting avenue through which to explore how culture impacts the expression of diversity in organizations.…”
Section: Organizational Culture and Diversitymentioning
confidence: 99%